An Experimental Study on Machining of AISI H - 13 Steel Using Dimple-Textured and Non-Textured Tungsten Carbide Cutting Tools. Issue 1 (January 2021) - Vignesh, G.; Barik, Debabrata; Aravind, S.; Ragupathi, P.; Arun, M.
Abstract: Fabrication of micro-dimples at the rack surface closer to the cutting region of the tungsten carbide tool will induce the tribological modifications at the tribo-contact surfaces. The motive of this work is to find the influence of micro-dimples fabricated on the cutting tools during turning operations. Linear arrays of dimple-textures with various geometrical aspects (dimple diameter and depth) and area density ratio were prepared using laser marking technique. The influence of surface-texture pattern is experimentally analysed through dry machining of AISI H – 13 steel using a dimple-textured tungsten carbide cutting tool. The responses of cutting temperature and cutting force generated during the turning operation were analysed. It shows improvement in machinability in terms of wear rate reduction in dimple-textured tools. Optimizing the dimension of micro-dimples (diameter of 90µm, depth of 60µm) results in a 10% reduction in tool wear rate.